Effect of a boomerang-shaped Conchal cartilage graft for Type three Tympanoplasty on Hearing - Elaprolu, Snigdha; Alexander, Arun; Ganesan, Sivaraman; Manu, Coimbatore Balakrishnan (International Archives of Otorhinolaryngology, 2020)
Introduction Chronic suppurative otitis media atticoantral disease (CSOM-AAD) is often associated with ossicular erosion resulting in significant hearing loss. Absence of the stapes suprastructure is a poor prognostic indicator of hearing outcome, which necessitates an effective reconstruction technique for ossicular continuity and restoration of middle ear volume. In the present study, we used a boomerang-shaped conchal cartilage graft.Objective To evaluate the improvement in hearing using a boomerang-shaped conchal cartilage graft for Type III tympanoplasty in cases of CSOM-AAD in which the stapes suprastructure was absent and to study the incidence of intraoperative/postoperative complications of this procedure.Method A total of 21 patients with CSOM-AAD who were found to have absent stapes suprastructure intraoperatively were included. A boomerang-shaped conchal cartilage graft was placed over the stapes footplate for reconstruction following canal wall down mastoidectomy. Pure tone audiogram (500, 1,000, 2,000 and 4,000 Hz) was done preoperatively and at 12 weeks postoperatively. Hearing outcome and incidence of complications were noted.Results There was a statistically significant reduction in the hearing loss for air conduction and air-bone gap (ABG) of 6.1 dB and 6.9 dB respectively (p < 0.05). Air-bone gap < 30 dB could be achieved in 71.4% of the patients as compared with 23.8% preoperatively. No significant difference was noted in the bone conduction threshold (p > 0.05). A better hearing outcome was observed at higher frequencies (2,000, 4,000 Hz). No major complications were encountered.Conclusion A boomerang-shaped conchal cartilage graft is effective when used for Type III tympanoplasty, especially at higher (2,000, 4,000 Hz) frequencies, and is comparable to newer materials such as titanium total ossicular reconstruction prosthesis (TORP). No major intraoperative/postoperative complications were noted.
Keywords: tympanoplasty; cartilage; graft; hearing; boomerang